Evaluation of oxidative stress indicators in lymphocytes of patients with alopecia areata - AL-Gaff A.N; Humadi S.; Wohaieb S.A; Muhi eldeen A.R (College of Pharmacy / Mustansiriyah University, 2005)
Alopecia areata is a nonscarring hair -loss condition that often has a patchy distribution and can be quite unpredictable.